Removal of PCBs by various white rot fungi in liquid cultures - Novotný, C; Vyas, B R; Erbanová, P; Kubátová, A; Sasek, V (Folia microbiologica, 1997)
The ability of Phanerochaete chrysosporium, Trametes versicolor, Coriolopsis polyzona, and Pleurotus ostreatus growing in a mitogen-limited mineral medium (NMM) to degrade PCBs in a commercial, Delor 106 mixture at a concentration of 0.9 ppm was compared. The respective amount of PCBs removed from the fungal cultures within 3 weeks were 25, 50, 41 and 0%. The capacities of the individual fungal species to remove PCBs correlated to some extent with their capabilities of decolorization of NMM agar containing both Poly R-478 or Remazol Brilliant Blue R dyes. Enzyme estimations indicated that both high and relatively stable activities of Mn-dependent peroxidase, Mn-independent peroxidase, lignin peroxidase, and laccase characterized efficient PCB degraders.
Keywords: Polychlorinated Biphenyls; Biodegradation, Environmental; polychlorované bifenyly; biodegradace; Polyporaceae